2019
DOI: 10.1038/s41598-019-43310-7
|View full text |Cite
|
Sign up to set email alerts
|

Bus bunching as a synchronisation phenomenon

Abstract: Bus bunching is a perennial phenomenon that not only diminishes the efficiency of a bus system, but also prevents transit authorities from keeping buses on schedule. We present a physical theory of buses serving a loop of bus stops as a ring of coupled self-oscillators, analogous to the Kuramoto model. Sustained bunching is a repercussion of the process of phase synchronisation whereby the phases of the oscillators are locked to each other. This emerges when demand exceeds a critical threshold. Buses also bunc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
104
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(107 citation statements)
references
References 33 publications
3
104
0
Order By: Relevance
“…Without any intervention, the two buses cannot remain staggered because such a configuration is unstable. This would be exemplified by systems with the buses moving at different natural frequencies, where frequency detuning leads to periodic bunching during lull periods, otherwise sustained bunching is the outcome during busy periods [1]. To prevent bunching, some form of intervention has to be executed.…”
Section: Stoppage Duration τmentioning
confidence: 99%
See 4 more Smart Citations
“…Without any intervention, the two buses cannot remain staggered because such a configuration is unstable. This would be exemplified by systems with the buses moving at different natural frequencies, where frequency detuning leads to periodic bunching during lull periods, otherwise sustained bunching is the outcome during busy periods [1]. To prevent bunching, some form of intervention has to be executed.…”
Section: Stoppage Duration τmentioning
confidence: 99%
“…Ref. [1] found that for the system served by N = 2 buses with f Let us now investigate the no-boarding policy applied to these situations in the NTU shuttle buses. We shall run simulations with the following setups:…”
Section: Quenciesmentioning
confidence: 99%
See 3 more Smart Citations